2019
DOI: 10.1002/pchj.320
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of Internet gaming disorder's symptoms on loneliness and aggression among undergraduate students and working adults in Malaysia

Abstract: Insufficient attention has been given to the integration of the mediating effect of Internet gaming disorder (IGD) symptoms on loneliness and four components of aggression-physical aggression, verbal aggression, anger, and hostility-in the Malaysian context. In the present study, 410 participants with (a) at least 1 year of Internet gaming experience and (b) between ages 20-to 39 years were recruited using the probability proportional to size sampling method. Participants were undergraduate students and workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
(67 reference statements)
2
13
0
Order By: Relevance
“…This study is the first attempt to extend the associations between PTSD/boredom and PTU into the context of the COVID-19 crisis. Our finding is also consistent with the recent studies on the relationship between loneliness and PTU during COVID-19 (e.g., Zhou and Leung, 2012 ; Boursier et al, 2020 ; T’ng et al, 2020 ). These findings support the compensatory model of PTU which asserts that the reactions to negative life circumstances (e.g., negative emotions due to COVID-19) might increase excessive Internet use and addictive-like symptoms ( Kardefelt-Winther, 2014a ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study is the first attempt to extend the associations between PTSD/boredom and PTU into the context of the COVID-19 crisis. Our finding is also consistent with the recent studies on the relationship between loneliness and PTU during COVID-19 (e.g., Zhou and Leung, 2012 ; Boursier et al, 2020 ; T’ng et al, 2020 ). These findings support the compensatory model of PTU which asserts that the reactions to negative life circumstances (e.g., negative emotions due to COVID-19) might increase excessive Internet use and addictive-like symptoms ( Kardefelt-Winther, 2014a ).…”
Section: Discussionsupporting
confidence: 93%
“…In turn, decreased loneliness may protect one from negative coping behaviors and PTU. Loneliness is a well-documented risk factor of PTU in the previous non-COVID-19 studies ( Seay and Kraut, 2007 ; T’ng et al, 2020 ). One study in Italian adults conducted during COVID-19 also reported a significant positive correlation between loneliness and SMA ( Boursier et al, 2020 ).…”
Section: Introductionmentioning
confidence: 89%
“…In terms of depression and anxiety, a positive association with IGD was consistently reported (Bonnaire & Baptista, 2019;C. De Pasquale et al, 2020;Männikkö, Billieux, & Kääriäinen, 2015;Mentzoni et al, 2011;Siste et al, 2021;Lutz Wartberg, Kriston, & Thomasius, 2017) with some studies reporting that IGD positively predicted the levels of depression and anxiety (Pontes, 2017;Wong et al, 2020). When focusing on depression or anxiety independently, Severo et al (2020) found a positive association between IGD symptoms and depressive symptoms, Singh, Dahiya, Singh, Kumar, and Balhara (2019) found that depressive symptoms predicted IGD, and Stavropoulos, Vassallo, Burleigh, Gomez, and Colder Carras (2021) found that IGD predicted higher depressive symptoms.…”
Section: Psychological Factors Associated With Igdmentioning
confidence: 97%
“…Alexithymia, a difficulty describing feelings, and physical aggression also predicted IGD symptoms (C. Evren, B. Evren, E. Dalbudak, M. Topcu, & N. Kutlu, 2019). Furthermore, T'ng, Ho, Sim, Yu, and Wong (2020) reported that IGD symptoms significantly predicted physical aggression, verbal aggression, anger, and hostility, while Lutz Wartberg, Kriston, Zieglmeier, Lincoln, and Kammerl (2019) found that IGD significantly predicted subsequent emotional distress one year later. These suggest that IGD is associated with a poor ability to manage negative emotional responses.…”
Section: Emotion Regulationmentioning
confidence: 99%
“…For this reason, loneliness causes individuals to develop a negative perception of themselves, such as being unwanted and not accepted by others and leads individuals to aggression, which is a method they use force to control other people in interpersonal relationships (Kurtyılmaz, 2011 ). Some studies show that loneliness results in higher levels of aggression (Anwar et al, 2019 ; T'ng et al, 2020 ; Yavuzer et al, 2019 ). The point that needs to be investigated here is how loneliness affects aggression.…”
Section: Introductionmentioning
confidence: 99%